2016
DOI: 10.1590/1807-1929/agriambi.v20n7p618-624
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of Regosol chemical atributes in guava management with neem under semi-arid conditions

Abstract: A B S T R A C TConsidering the relevant importance of guava (Psidium guajava) in Northeastern Brazil along with the benefits of neem cake amendments on soil characteristics, this work evaluated the effects of neem cake on chemical attributes of a Regosol under irrigated guava orchard in an alluvial valley of Pernambuco semi-arid region. Evaluations were carried out in two areas (area 1 -with neem cake; area 2 -without neem cake) at three periods: before the first application of neem cake, 90 days after the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Similar findings were reported by Grego et al, (2010), who discovered that pH had the lowest CV (3.5%) and the low variation. In all sampling periods and both locations, pH was the only one with minimal change (Castro et al, 2016). Additionally, high and low pH values of geographic variability have been documented in earlier research (Caniego et al, 2005& Vidal Vázquez et al, 2013.…”
Section: Soil Property Descriptionsupporting
confidence: 75%
“…Similar findings were reported by Grego et al, (2010), who discovered that pH had the lowest CV (3.5%) and the low variation. In all sampling periods and both locations, pH was the only one with minimal change (Castro et al, 2016). Additionally, high and low pH values of geographic variability have been documented in earlier research (Caniego et al, 2005& Vidal Vázquez et al, 2013.…”
Section: Soil Property Descriptionsupporting
confidence: 75%
“…Other studies have also found a smaller variation in soil pH compared to other soil physical-chemical attributes (Castro et al, 2016;Laekemariam et al, 2018;Sharma et al, 2020). Low pH variability occurs because the pH values are the logarithmic scale of proton concentration in the soil solution, so this variability would be greater if soil acidity were directly expressed in terms of proton concentration (Reza et al, 2017;Moharana et al, 2020).…”
Section: Attributesmentioning
confidence: 95%
“…Classic statistical analysis was carried out and normality was evaluated by the Kolmogorov-Smirnov test at 0.05 probability level. Thirty soil samples were randomly selected from each field, as suggested by Castro et al (2016), in order to conduct the statistical analysis. The coefficient of variation (CV) was classified according to Warrick & Nielsen (1980) criteria as follows: Low variability (CV < 12%), intermediate variability (12 ≤ CV ≤ 60%), and high variability (CV > 60%).…”
Section: Methodsmentioning
confidence: 99%